Analysis of Gowa Regency's Leading Economic Sectors - As'ad, Ajmal; Mulang, Hastuti (Economos : Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this research is to analyze and find out what sectors are included in the base sector, changes and shifts in the economic sector and the classification of economic sector growth in Gowa Regency. The data analysis method is Location Quotient (LQ) analysis from secondary data which is time series data for the last 4 years (2018-2021) of the Central Bureau of Statistics South Sulawesi. The results of Location Quotient (LQ), Shift Share (SS), and Klassen Typology analysis show that in Gowa Regency the leading sectors before the Covid-19 pandemic (2012-2019) were the electricity and gas procurement sector; water supply, waste management and recycling sectors; and the real estate sector. Meanwhile, there were changes during the Covid-19 pandemic (2020-2021) where the agriculture, forestry, and fisheries sectors; information and communication sector; and the government administration, defense, and compulsory social security sectors are the leading sectors in Gowa Regency. Based on the analysis, these sectors are base sectors (LQ>1), competitive sectors or have high competitiveness (positive Differential Shift), and include advanced and fast-growing sectors (quadrant I).